El frijol en El Salvador: implicaciones para la investigacion agricola - Portillo de Villegas, ME; Gaona R, J (International Center for Tropical Agriculture, 1991)
Results of a study on bean cultivation in El Salvador are given. Aspects analyzed were as follows: consumption structure (apparent, per capita, and rural-urban; preferences, consumption and cooking ways, and nutritive value); area, production, and yields (at national and regional levels, by cropping system, and by planting time), production constraints (abiotic, biotic, and technological factors), and production perspectives. Recommendations are included on future research activities. (CIAT)